CAREER INDECISION (Annual of the Faculty of Philosophy in Skopje, 2020)
In this paper career indecision as a complex and multidimensional constructthat attracts considerable research interest in the field of vocational psychology is presented. The introductory part describes this construct through one of the most commonly used definitions and the negative outcomes it can cause. The second part explains how the career indecision is integrated into the vocational theories/theories of career choice and development, followed by an overview of the empirical findings on itsstructure and causes of cognitive and emotional nature. The distinction between careerindecision and indecisiveness, as well as the difference between developmental, chronicand acute career indecision are explained in the last part. In the conclusion part the importance of the career indecision for vocational guidance and career counselling is emphasized.
Keywords: CAREER INDECISION; CAREER CHOICE; STRUCTURE